Incidence and determinants of hysterectomy among North Indian women: An 8-year follow-up study - Rajkumari, Sunanda; Chaudhary, Vineet; Kasaudhan, Sapana; Saraswathy, Kallur Nava (Frontiers in Public Health, 2022)
Background Despite indications of a rapid increase in the number of hysterectomies performed in India, very few studies have methodically investigated the rate and determinants of the incidence of hysterectomy. The present study aims to estimate the rate of incidence of hysterectomy and identify predictors/determinants of incident hysterectomy in a cohort of North Indian women. Methods In the present study, a cohort of 1,009 ever-married North Indian women (aged 30–75 years) was followed up after a median of 8.11 years. Those hysterectomized at the baseline (63) were excluded; and of the rest 946 participants, 702 (74.2%) could be successfully followed-up. During the baseline assessment, data about sociodemographic variables, reproductive history, menopausal status, physiological health, and selected blood biochemicals were collected. During the end-line assessment, data about sociodemographic variables, current menopausal status, and incident hysterectomy were recorded. Results The overall rate of incidence of hysterectomy was found to be 11.59 per 1,000 women-years, in the study population. Interestingly, the incidence rates were found to be similar among pre- and post-menopausal women. Further, while late age at menarche was found to be negatively associated with incident hysterectomy, folate repletion and high triglyceride (TG) at the baseline were found to be positively associated. Conclusions High rate of incident hysterectomy in the studied population points toward the huge burden of gynecological morbidity and the unavailability of non-invasive protocols. Such a situation warrants immediate policy intervention. Further, maintaining TG and folate within normal physiological ranges may be beneficial in gynecological ailments necessitating hysterectomy.